INFLUENCE OF GNOSTIC AND STEREOGNOSTIC FUNCTIONS ON FOOTBALL ACTIVITIES - Patrik Beňuš; Ján Gemmel; Dávid Líška; Daniel Gurín (Matej Bel University, 2021)
Finding talent for sports is hard. Testing for the selection of a talented child in football is very common today. In our study we compared gnostic function, test individual football gaming activities and evaluate their performance in matches. The sample consists of 23 football players in U12 and U13 category who participated in testing of individual gaming activities and gnostic abilities. Testing was performed during 4 weeks beginning with participants who have completed their game activities of individuals on artificial grass. Identity testing from 4 tests - control ball, slalom with ball, accuracy passing, accuracy shooting. After completing this examination, we tested the gnostic and stereognostic functions, which we then compared to abovementioned tests. Gnostic functions were tested by 3 standardized tests - kinesthesis test, body image (foot), Petrie test. And another 3 non-standardized (modified/invented by us) - step test, tread test a step calculation test. Finally, we collected data about other beneficiaries during the 2019/2020 first part of season. Only moderate to weak correlation between slalom with ball and step test (dominant DK) was found r = -0.39 and correlation between slalom with ball and body image test (foot) r = 0,4. There was also found a significant correlation between the Preferred Test and the Stage Test (non-dominant DK) r = 0.33; Examination of other tests correlated between kinetics tests, for the dominant HK do r = 0.37. In our study, we have not shown significant correlations between individual tests and neither between both tests and performance during the match. We may recommend obtaining additional data that could bring valuable information to the next study.